2009
DOI: 10.1111/j.1460-9592.2009.03129.x
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture management of pain and emergence agitation in children after bilateral myringotomy and tympanostomy tube insertion

Abstract: Our study suggests that acupuncture therapy may be effective in diminishing both pain and emergence agitation in children after BMT insertion without adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 21 publications
2
61
0
Order By: Relevance
“…[52][53][54][55][56][57][58][59][60] One study found acupuncture partly effective for pain, 61 and one study found acupressure effective for vomiting, but not nausea.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[52][53][54][55][56][57][58][59][60] One study found acupuncture partly effective for pain, 61 and one study found acupressure effective for vomiting, but not nausea.…”
Section: Resultsmentioning
confidence: 99%
“…58 One study reported on acupuncture applied to the PC6 acupoint to treat sore throat due to intubation. 56 Acupuncture or acupressure was initiated before the induction of anesthesia in seven studies, 52,53,55,62,[64][65][66] during anesthesia in five studies, 37,56,[58][59][60] and postoperatively in three studies. 54,57,61 One study tested both preoperative and perioperative acupuncture.…”
Section: Norheim Et Almentioning
confidence: 99%
See 3 more Smart Citations